Legal consequences of unilateral cancellation of the home ownership credit agreement at PT Rudensia Jaya Raya - Joko Widhianto; Fitika Andraini (Trigin Publisher, 2023)
Home is a primary need for most families, both living in rural and urban areas, which is a primary need. The fulfillment of these primary needs cannot be fulfilled by everyone by buying in cash. Therefore, a financial institution is needed to provide financial assistance in the form of lending, particularly in the form of Home Ownership Loans (KPR). The purpose of this research is to find out the sale and purchase agreements for houses at PT. Rudensia Jaya Raya and the legal consequences of the unilateral cancellation of the house sale and purchase agreement by consumers at PT. Rudensia Jaya Raya. By using a statutory approach and a fact approach. House sale and purchase agreement at PT. Stages of Rudensia Jaya Raya include booking fees or receipts, selection of building designs, and making payments in cash or with housing loans, if the KPR stages are payment of booking fees, advances for credit agreements and PPJB. If the mortgage has been approved by the bank, then proceed with the construction of the house.%MCEPASTEBIN%